Studies on Haloperidol and Adjunctive α-Mangostin or Raw Garcinia mangostana Linn Pericarp on Bio-Behavioral Markers in an Immune-Inflammatory Model of Schizophrenia in Male Rats - Lotter, Jana; Möller, Marisa; Dean, Olivia; Berk, Michael; Harvey, Brian H. (Frontiers in Psychiatry, 2020)
Schizophrenia is a severe brain disorder that is associated with neurodevelopmental insults, such as prenatal inflammation, that introduce redox-immune-inflammatory alterations and risk for psychotic symptoms later in life. Nutraceuticals may offer useful adjunctive benefits. The aim of this study was to examine the therapeutic effects of Garcinia mangostana Linn (GML) and one of its active constituents, α-mangostin (AM), alone and as adjunctive treatment with haloperidol (HAL) on schizophrenia related bio-behavioural alterations in a maternal immune-activation (MIA) model. Sprague Dawley dams were exposed to lipopolysaccharide (LPS) on gestational days 15 and 16. Male offspring were treated from PND 52 - 66 with either vehicle, haloperidol (HAL; 2 mg/kg), GML (50 mg/kg), HAL+GML, AM (20 mg/kg) or HAL+AM. Control dams and control offspring were treated with vehicle. In order to cover the mood-psychosis continuum, prepulse inhibition (PPI) of startle, locomotor activity and depressive-like behaviour were assessed on PND’s 64-65, followed by assay of frontal-cortical lipid peroxidation and plasma pro-inflammatory cytokines, viz. interleukin-1 (IL-1) and tumour necrosis factor-α (TNF-α). MIA-induced deficits in sensorimotor gating were reversed by HAL and HAL+GML, but not GML and AM alone. MIA-induced depressive-like behaviour was reversed by AM and GML alone and both in combination with HAL, with the combinations more effective than HAL. MIA-induced cortical lipid peroxidation was reversed by HAL and AM, with elevated IL-6 levels restored by GML, AM, HAL and HAL+GML. Elevated TNF-α was only reversed by GML and HAL+GML. Concluding, prenatal LPS-induced psychotic- and depressive-like bio-behavioural alterations in offspring are variably responsive to HAL, GML and AM, with depressive (but not psychosis-like) manifestations responding to GML, AM, and combinations with HAL. AM may be a more effective antioxidant than GML in vivo, although this does not imply an improved therapeutic response, for which trials are required.